PENGARUH POLA ASUH ORANG TUA TERHADAP PENYESUAIAN DIRI SISWA KELAS I DITINJAU DARI JENIS KELAMIN - annisa, Ismi Choiron (Universitas Pendidikan Indonesia, 2020)
This research to determine the effect of parenting and gender on student adjustment, as well as knowing the interaction between parenting and gender on the adjustment of elementary school students in Class I. This research uses a quantitative approach to the type of expost facto research. The sample of this research was grade I students who were chosen by random sampling. Data analysis techniques using two-way anava with interaction. The results showed that there was an influence between parenting parents on students' self-adjustment with a value of F1 = 15.8> F0.01 (1; 54) = 7.08, which means that there was a significant influence between the tendency of parenting parents towards adaptation student. The second result shows that there is an influence between gender on students' self-adjustment with a value of F2 = 6.5> F0.01 (2; 54) = 4.98. While the value of F3 = 0.04